Pathogenesis guided therapeutic management of COVID-19: an immunological perspective. (4th March 2021) - Kumar, Ashutosh; Prasoon, Pranav; Sekhawat, Prakash S.; Pareek, Vikas; Faiq, Muneeb A.; Kumari, Chiman; Narayan, Ravi K.; Kulandhasamy, Maheswari; Kant, Kamla
Abstract: Lack of standardized therapeutic approaches is arguably the significant contributor to the high burden of mortality observed in the ongoing pandemic of the Coronavirus disease, 2019 (COVID-19). Evidence is accumulating on SARS-CoV-2 specific immune cell dysregulation and consequent tissue injury in COVID-19. Currently, no definite drugs or vaccines are available against the disease; however initial results of the ongoing clinical trials have raised some hope. In this article, taking insights from the emerging empirical evidence about host-virus interactions, we deliberate upon plausible pathogenic mechanisms and suitable therapeutic approaches for COVID-19.